PSIKOEDUKASI POLA ASUH DENGAN METODE (CIUM, PELUK, BERI ASUPAN) UNTUK MENINGKATKAN PENGETAHUAN ORANG TUA - Syahidah, Najmah Faiha Nurul; Berry, Yunike; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2024)
This study aims to enhance the knowledge and skills of parents in Sirnajati Village regarding responsive and affectionate parenting using the CILUKBA (Kiss, Hug, and Provide Nutrition) method. This method integrates aspects of parenting style, developmental stimulation, and nutritional intake to support optimal child growth and development. The psychoeducation activity was conducted as a full-day pschoeducation involving 15 parents aged 20-35 years. The program included socialization about the importance of emotional interaction and attention to child nutrition, practical training on the CILUKBA method, simulation of method application, and self-evaluation. The results showed a significant increase in the participants' knowledge and parenting skills. Before the training, 9 participants were categorized as low in parenting knowledge, whereas after the training, 12 participants reached a high category. Participants reported improved emotional connection with their children and a better understanding of the importance of balanced nutrition. The program effectively enhanced parenting quality and positively impacted child development.